Biophysical parameters of the oral fluid and cells of the buccal epithelium in children with diseases of the thyroid gland in the course of orthodontic treatment of maxillodental anomalies. - Kolesnik, K. A.; Denga, E. M. (Medicni Perspektivi, 2014)
The thyroid status disturbance may be reflected on the biological processes which underlie orthodontic tooth movement. Aim of research – to study state of the oral fluid and buccal epithelium cells (BEC) in the course of a complex orthodontic treatment of children with thyroid gland diseases. In 79 children with a diffuse nontoxic goiter (DNG) of the I-III degrees, stability of oral fluid pH (ΔpH), rate of mobile nuclei of BEC, ratio of electrophoretic displacement range of nuclei and plasmolemms was estimated. Estimation of corresponding parameters in the initial state, in 1, 3, 6 and 8 months after fixation of the fixed orthodontic apparatus was carried out. Children of the basic group according to pathology degree in addition received a prophylactic complex including preparations: “Vitrum Perfomens", "Teraflex", "Kalcicor", «Potassium iodide», «Echinacea compositum C», "Lizodent", "Osteobios". Application of the prophylactic complex in orthodontic treatment of children with DNG prevented growth of ΔрН after fixation of brackets. Throughout all time of supervision it promoted reduction of this rate which slightly exceeded average rate for the given age of children in 8 months. Application of this prophylactic complex already in 1 month after fixation of brackets has raised quantity of mobile BEC nuclei by 44% and by 1,64 times has increased the relation of ranges of plasmolemms and nuclei displacement. In 8 months of supervision percent of mobile nuclei BEC and the relation of Apl/Aya in the basic group was by 2 times more, than in a comparison group, approaching to average rate. Сhildren with thyroid gland diseases need active treatment-and-prophylactic measures at stages of active apparatus treatment. The developed therapeutic complexes of orthodontic treatment of maxillo-dental anomalies in children with DNG allows to effectively support and improve functional reactions in the organism and in the oral cavity, compensating stressful action of fixed orthodontic apparatuses.